THE PATTERN OF AMERICAN RHETORIC ON THE SPIRIT OF MISSION: AN ANALYSIS ON THE TEXT OF BUSHS INAUGURAL ADDRESS - Mister Gidion Maru (Celt: A Journal of Culture, English Language Teaching & Literature, 2016)
As a textual study, this research paper aims at elaborating the rhetorical patterns in the American mind by examining the inaugural addresses George W Bush particularly on the spirit of mission. The study on this topic becomes urgent to be discussed in relation to the importance of understanding a rhetoric pattern in terms of developing teaching material for cross cultural awareness and language skills. The choosing of the presidents inaugural address as the mental evidences is not apart from the synthesis that they represents a formal speech which covers the socio-cultural aspects and they will bring a certain pattern of rhetoric in their attempt to communicate with public. For the purpose of achieving the aim of this research, the library research is carried out by applying Goffman?s Frame Analysis. The results show that the president constructs a certain pattern of rhetoric by using the Puritan expressions particularly for engaging American people with the spirit of mission. The rhetoric patterns are found to convey the national and world mission. The expressions used in the inaugural addresses seem to meet with peoples expectations as a new presidency is begun